THE DURATION OF GADGET USE WITH DISABILITY LEVEL IN TEXT NECK SYNDROME ON WIDYA MANDALA CATHOLIC UNIVERSITY STUDENTS SURABAYA - Leandro Vierry Santoso; Pauline Meryana; Steven Wijono (JOURNAL OF WIDYA MEDIKA JUNIOR, 2023)
Background: Technological advances in the telecommunications sector are experiencing rapid development. This lead to increasing gadget usage, which can cause neck pain, known as text neck. Objective: To determine the relationship between the duration of gadget use and the level of disabilities in text neck syndrome among students of UKWMS.Methods: This research used a cross-sectional design with a non-probability sampling technique, held from July 20-August 23, 2022, via questionnaire. The population of this study was UKWMS students, with a total sample of 203 subjects. The subjects entered into five groups namely group A(1-<2 hours), B(2-<3 hours), C(3-<4 hours), D(4-<5 hours), and E(≥ 5 hours). Then, it split using the NDI into without text neck, mild, moderate, severe, and complete disability.Results: In group A, without text neck five subjects. In group B, 23 subjects without text neck, and six with mild. In group C, there were 23 people without text necks, eight people with mild, and one subject with moderate. In group D, there were 22 people without text necks, 14 people with mild, and one with severe. In group E, there were 82 people without text necks, 17 people with mild, and one with severe. There were no complete disabilities in this study. Data were analyzed using the Spearman correlation test, which yielded p=0.396 (p>0.05).Conclusion: There’s no relationship between the duration of gadget use and the level of disability in text neck syndrome in UKWMS students.